2020
DOI: 10.1096/fj.202000111rr
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of γH2AX+ cells in skeletal muscle from aged and obese humans

Abstract: Over the past 20 years, various identifiers of cellular senescence have been used to quantify the abundance of these cells in different tissues. These include classic markers such as p16, senescence-associated β-gal, and γH2AX, in addition to more recent markers (Sudan Black B and HMGB1). In vivo data on the usefulness of these markers in skeletal muscle are very limited and inconsistent. In the present study, we attempted to identify senescent cells in frozen human skeletal muscle biopsies using these markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 88 publications
4
43
0
Order By: Relevance
“…Both BMI and waist circumference were positively associated with DNA damage ( 94 ). Similar findings were made in an aging study, where obesity was a stronger predictor of skeletal muscle DNA damage compared to aging ( 96 ). In preclinical work, obese zucker rats were found to have increased levels of DNA damage in several organ sites as measured by frequency of cells staining positive for phosphorylated histone variant H2AX (γH2AX), a marker of double strand breaks in DNA ( 97 ).…”
Section: Obese Breast Adipose-derived Sources Of Dna Damagesupporting
confidence: 85%
“…Both BMI and waist circumference were positively associated with DNA damage ( 94 ). Similar findings were made in an aging study, where obesity was a stronger predictor of skeletal muscle DNA damage compared to aging ( 96 ). In preclinical work, obese zucker rats were found to have increased levels of DNA damage in several organ sites as measured by frequency of cells staining positive for phosphorylated histone variant H2AX (γH2AX), a marker of double strand breaks in DNA ( 97 ).…”
Section: Obese Breast Adipose-derived Sources Of Dna Damagesupporting
confidence: 85%
“…Increasing p16 INK4a expression during cellular aging is also an intrinsic mechanism to lower mitotic error of aged stem cells [4]. Since most of cells within the human body are short-AGING lived [5], p16 INK4a+ senescent cells are widely detectable in embryonic [6] and young adult tissues [7][8][9]. Lymphocyte p16 INK4a mRNA increases exponentially with age from 18 to 80 years old [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study had attempted to quantify senescent cells in human skeletal muscle using the phosphorylated form of the histone H2A variant gamma-H2AH (γH2AX) as a marker of DNA damage. In muscle cell biopsy of young subjects compared to elderly ones, the latter did not show a significant increase of senescent cells [52]. Interestingly, the same study demonstrated a higher cells senescence and senescence-associated secretory phenotype in muscle from obese individuals and in in vitro obesogenic environments, suggesting that DNA damage, which may reduce the function of the muscle, is more directly linked to obesity than aging.…”
Section: Skeletal Myogenesis and Sarcopeniamentioning
confidence: 78%